2014
DOI: 10.1177/1535370214558024
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot juice reduces infarct size and improves cardiac function following ischemia–reperfusion injury: Possible involvement of endogenous H2S

Abstract: Ingestion of high dietary nitrate in the form of beetroot juice (BRJ) has been shown to exert antihypertensive effects in humans through increasing cyclic guanosine monophosphate (cGMP) levels. Since enhanced cGMP protects against myocardial ischemia-reperfusion (I/R) injury through upregulation of hydrogen sulfide (H 2 S), we tested the hypothesis that BRJ protects against I/R injury via H 2 S. Adult male CD-1 mice received either regular drinking water or those dissolved with BRJ powder (10 g/L, containing $… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“… 30 LAD 24 R Pentobarbital SEM 6 45.5 5 6 10.2 3.9 41 Salloum et al [ 52 ] d Mouse M 32.2 ± 0.4 g Cinaciguat Post (10 µg/kg) as a bolus 5 min before reperfusion i.v. 30 LAD 24 R Pentobarbital SEM 6 43.0 1.5 6 16.5 3.7 42 Salloum et al [ 53 ] Mouse M 28–33 g Beetroot juice Pre (10 g/L) in drinking water for 7 days before ischemia p.o. 30 LAD 24 R Pentobarbital SEM 6 46.5 3.5 6 15.8 3.2 43 Sivarajah et al []55 Rat M 220–300 g NaHS Pre (3 mg/kg) as a bolus 15 min before ischemia i.p.…”
Section: Methodsmentioning
confidence: 99%
“… 30 LAD 24 R Pentobarbital SEM 6 45.5 5 6 10.2 3.9 41 Salloum et al [ 52 ] d Mouse M 32.2 ± 0.4 g Cinaciguat Post (10 µg/kg) as a bolus 5 min before reperfusion i.v. 30 LAD 24 R Pentobarbital SEM 6 43.0 1.5 6 16.5 3.7 42 Salloum et al [ 53 ] Mouse M 28–33 g Beetroot juice Pre (10 g/L) in drinking water for 7 days before ischemia p.o. 30 LAD 24 R Pentobarbital SEM 6 46.5 3.5 6 15.8 3.2 43 Sivarajah et al []55 Rat M 220–300 g NaHS Pre (3 mg/kg) as a bolus 15 min before ischemia i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Beet juice is commonly used as a supplement because of its high quantity of inorganic nitrate, a compound found naturally in vegetables and processed meats [ 210 ]. Nitrate is believed to produce cardiovascular benefits, such as protecting against myocardial ischemia/reperfusion, vascular dysfunction, and hypertension in mice and rats [ 211 , 212 ]. A study found decreased nitrate and increased nitrite contents in home-made raw beet, carrot, and radish juices after 48 h of storage at ambient temperatures.…”
Section: Nutraceuticals In the Treatment Of Pulmonary Arterial Hypmentioning
confidence: 99%
“…This effect of alpha lipoic acid may be related to the release of sulfur sulfur and H 2 S ( Dudek et al, 2014 ). The intake of beetroot juice (BRJ) prevents myocardial infarction and ventricular dysfunction after I/R in adult male CD-1 mice through CSE-mediated endogenous H 2 S production ( Salloum et al, 2015 ). Na 2 S administration can reduce infarct size induced by myocardial I/R injury in db/db mice ( Peake et al, 2013 ).…”
Section: H 2 S and Cardiovascular Diseasesmentioning
confidence: 99%